Effect of aqueous and oil-based formulations of 13 native isolates of Beauveria bassiana (Ascomycota) on Rhodnius prolixus (Triatominae) under experimental conditions - Cazorla Perfetti, Dalmiro (2017)
Rhodnius prolixus is the main vector of Chagas disease in Venezuela. The present study aimed to evaluate the effect of aqueous and 50% soy bean oil-based formulations (1x107 conidia/ml) of 13 native Beauveria bassiana (Fungi: Ascomycota) isolates on fourth instar nymphs of Rhodnius prolixus. The conidial suspension were used under laboratory conditions (26 ºC; RH >90%). The treatment was by immersion and mortality and conidiation were evaluated daily for 24 days. The results showed that the fungal soy-bean oil formulations tested were more effective than the aqueous suspension, as attained significantly higher mortality and efficacy percentages and decreased LT50 in the 13 isolates (p88%). LF14 and LF13 isolates showed a higher percentage of accumulated mortality, efficacy and a lowest LT50 in aqueous formulations as well as in oil-based ones. These B. bassiana isolates appears to be considered as good candidates to be tested under field conditions in biorational control programmes for Chagas disease vectors.